2013
DOI: 10.4316/aece.2013.01015
|View full text |Cite
|
Sign up to set email alerts
|

Segmentation of Bone Structure in X-ray Images using Convolutional Neural Network

Abstract: The segmentation process represents a first step necessary for any automatic method of extracting information from an image. In the case of X-ray images, through segmentation we can differentiate the bone tissue from the rest of the image. There are nowadays several segmentation techniques, but in general, they all require the human intervention in the segmentation process. Consequently, this article proposes a new segmentation method for the X-ray images using a Convolutional Neural Network (CNN). In pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(29 citation statements)
references
References 18 publications
0
27
0
Order By: Relevance
“…There have been a couple of previous works that applied CNN methods for medical image segmentation tasks [17, 18, 20–22]. The basic method is a patch-wise classification process.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been a couple of previous works that applied CNN methods for medical image segmentation tasks [17, 18, 20–22]. The basic method is a patch-wise classification process.…”
Section: Methodsmentioning
confidence: 99%
“…Many approaches have been applied to overcome this limitation, including post-processing, increasing the size of image patches and using location information as part of the input of CNN, etc. [17, 18, 21, 22]. …”
Section: Methodsmentioning
confidence: 99%
“…CNNs have also been applied to X-ray image processing applications. Here, CNNs have been used to detect bone [11]. Recently, segmentation of blood vessels has been introduced as another application of using CNNs on retinal photographs [12].…”
mentioning
confidence: 99%
“…CNNs, often referred to as deep learning, are representation-learning methods [25] that were recently shown to significantly outperform other machine vision techniques in many applications, including large-scale natural image classification [26]. While most examples of applications to X-ray imagery to date have been limited to medical data [27], Akçay et al [28] recently demonstrated the use of CNNs for baggage X-ray image classification. As there was insufficient training data to train a network from scratch, the authors fine-tuned a variant of the AlexNet architecture [29] that was pre-trained on ImageNet, a dataset of natural images.…”
Section: Related Workmentioning
confidence: 99%